Reflections of nursing students, lecturers, and clinical supervisors in the Western Cape on large classes - Fakude, L (South African Journal of Higher Education, 2016)
Nursing education in the Western Cape responded to the South African higher education transformation agenda by establishing a Common Teaching Platform (CTP) for the delivery of the undergraduate nursing programme. Three universities collaborated since 2005 in the delivery of this programme in the region. One of the universities was identified as the enrolling institution. During this period, the province was experiencing a shortage of nursing personnel. In response to this shortage and to the transformation in the country, there was an increase in the enrolment target for the undergraduate programme offered by the three collaborating universities. After 5 years of the establishment of the Common Teaching Platform and the increase student intake, there was a need to assess how the lecturers and clinical supervisors experienced teaching large classes. In this article, the experiences of nursing students, clinical supervisors, and lecturers are shared and suggestions from the target groups are reflected.